The impacts of translocation on the cultural evolution of song in the North Island saddleback or tieke (Philesturnus rufusater) : a thesis presented in partial fulfilment of the requirements for the degree of Docotor of Philosophy in Ecology at Massey University, Auckland, New Zealand - Parker, Kevin Alan (Massey University, 2011)
The IUCN (1987) defines a translocation as a release of animals with the intention of establishing, re-establishing, or augmenting an existing population. The origins of translocation practise are very much in applied conservation management. However, translocations also provide other outputs. They provide a means by which the general public might connect and commit to conservation and they provide unique opportunities for scientific research because the age and source of founder populations are completely known. Geographical isolation plays a crucial role in speciation events. Thus studies of divergence of behavioural signals in isolated populations have been critical to understanding how barriers to gene flow develop. Bird song is a vital conspecific recognition signal (CRS) and many studies have demonstrated significant geographical variation in song with several hypotheses posed to explain this variation. However, a key problem in testing these hypotheses is an inability to measure the pace of song divergence. This is because the timing and source of founder events are rarely detected. Here I use the NI saddleback or tīeke (Philesturnus rufusater) isolated on a single island in 1964 but subsequently increased by translocation to 13 island populations, to show that significant geographical variation in song can develop in less than 50 years. Furthermore, my data shows a clear signal of serial population bottlenecks (up to 3 times) following translocation and supports both bottleneck and cultural mutation hypotheses in explaining this variation. Critically NI saddleback discriminate between songs from different islands and this discrimination might lead to an eventual reduction in effective population size. This illustrates the potential for human induced founder and isolating events, including conservation management, to be microevolutionary events and challenges us to consider the implications of conservation biology in an evolutionary context.
Keywords: Bird song; Bird relocation; Bird populations